Harvey’s Revised Mental Model Applied to Brazil's Exchange Rate under unique economic events: the Covid-19 pandemic and the Russo-Ukrainian war - Douglas Alencar; Lúcio Otávio Seixas Barbosa (Cadernos CEPEC)
This article analyzes the exchange rate path in Brazil during the Covid-19 pandemic and the Russo-Ukrainian war using the dynamic for determining the exchange rate proposed by Harvey (2009). The Harvey mental model was reviewed to consider the targeting inflation framework, which guide the Central Bank’s actions and influences financial market agents’ expectations. Thus, the research question that guides this work is: Is it possible to understand the short-term dynamics of the nominal exchange rate in Brazil under the Covid-19 pandemic and the Russo-Ukrainian war using the revised Harvey model (2009)? Brazil was chosen as one of the largest countries in Latin America and one of the most important emerging countries. To answer the research question, a theoretical review was carried out regarding the exchange rate speculation strategies used by Keynes. Subsequently, Harvey’s model was presented and amended to consider the role of the inflation targeting model in determining the short-term nominal exchange rate and the impact of these unique events. Then, an analysis of agents’ expectations of the mental model variables and of the exchange rate dynamics was performed. The results suggest that the revised Harvey model (2009) is useful to understand the path of nominal exchange rate although, under the Covid-19 outbreak, agents wrongly predicted it.